Entrepreneurship in the public enterprises in the Republic of Macedonia - conditions and perspectives - Petkovska Mirchevska, Tatjana; Georgieva Svrtinov, Vesna; Petkovski, Vladimir (Economic Development, Journal of the Institute of Economics – Skopje, 2018)
Companies that are owned, managed and controlled by the state or local government are called public sector enterprises or public enterprises. The primary goal of these enterprises is to increase social welfare and protect the public interest, unlike private sector companies whose main goal is to make a profit. The satisfaction of citizens as users of public services is crucial for every institution that offers public services. When for a particular service there is a high level of satisfaction from the users (citizens), this mean that the service is of high quality. By changing entrepreneurial skills in the operation of public enterprises, the quality of public services and thus the citizen satisfaction is improved, which is reflected by a positive change in their behavior. In this way, the confidence in the public institutions is significantly enhanced and the level of satisfaction of the citizens with the use of these services is increased. Therefore, the promotion of entrepreneurial skills in the operation of public enterprises is of particular importance. The main objective of the research is to analyze the application of entrepreneurial skills among the public enterprises in the country and to give directions for improvement of the entrepreneurial skills that will result in raising the quality of public services and a greater level of satisfaction among the citizens as their beneficiaries. The subject of the research in the paper is theoretical and empirical elaboration to emphasize the role and importance of entrepreneurship in public enterprises in the modern environment, to set guidelines for its wider application in order to raise the quality of public services and to meet the needs of citizens as users of these services
Keywords: entrepreneurship, public enterprises, public services, public sector